Volatile profile of yellow passion fruit juice by static headspace and solid phase microextraction techniques - Braga,Gilberto Costa (2015)
The profile of volatile compounds of yellow passion fruit juice was analyzed by solid phase microextraction headspace (HS-SPME) and optimized static headspace (S-HS) extraction techniques. Time, temperature, NaCl concentration and sample volume headspace equilibrium parameters was adjusted to the S-HS technique. The gaseous phase in the headspace of samples was collected and injected into a gas chromatograph coupled to a mass spectrometer. In the HS-SPME technique was identified 44 volatile compounds from the yellow passion fruit juice, but with S-HS only 30 compounds were identified. Volatile esters were majority in both techniques, being identified ethyl butanoate, ethyl hexanoate, (3z)-3-hexenyl acetate, hexyl acetate, hexyl butanoate and hexyl hexanoate. Aldehydes and ketones were not identified in S-HS, but were in HS-SPME. β-Pinene, p-cymene, limonene, (Z)-β-ocimene, (E)-β-ocimene, γ-terpinene, α-terpinolene and (E) -4,8-dimethyl-1, 3,7 - nonatriene terpenes were identified in both techniques. This study showed that the S-HS optimized extraction technique was effective to recovery high concentrations of the major volatile characteristics compounds in the passion fruit, such as ethyl butanoate and ethyl hexanoate, which can be advantageous due to the simplicity of the method.